2017
DOI: 10.17576/jsm-2017-4606-03
|View full text |Cite
|
Sign up to set email alerts
|

Biological Aspects of Channa limbata (Cuvier, 1831) in Ta Bo - Huai Yai Wildlife Sanctuary, Phetchabun Province, Thailand

Abstract: The biological aspects of Channa limbata were studied between November 2013 and October 2014

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…A negative allometric growth pattern in the present study has also been reported for C. striata from Agusan Marsh, Philippines [7], C. diplogramma from Lake Vembanad, India [6],C. limbata from Ta Bo -HuaiYai Wildlife Sanctuary, Thailand [46] and C. obscura from Ologe Lagoon, Nigeria [47]. Our finding was contrary to C. striatus from Uttar Pradesh, India [5]; C. punctata from Gomti River, India [48] and Parachannaobscura from Buyo reservoir, West Africa [49], in which exhibited positive allometric growth pattern (b> 3).…”
Section: Length-weight Relationshipsupporting
confidence: 83%
“…A negative allometric growth pattern in the present study has also been reported for C. striata from Agusan Marsh, Philippines [7], C. diplogramma from Lake Vembanad, India [6],C. limbata from Ta Bo -HuaiYai Wildlife Sanctuary, Thailand [46] and C. obscura from Ologe Lagoon, Nigeria [47]. Our finding was contrary to C. striatus from Uttar Pradesh, India [5]; C. punctata from Gomti River, India [48] and Parachannaobscura from Buyo reservoir, West Africa [49], in which exhibited positive allometric growth pattern (b> 3).…”
Section: Length-weight Relationshipsupporting
confidence: 83%
“…The young mother spawning for the first time produces small eggs (about 0.8 mm diameter); the productive females will produce large eggs (about 1 mm) and old females again producing small eggs (about 0.8 mm). A relationship between length, weight, and fecundity for the family Channidae was well-documented in C. gachua (Gaikwad et al, 2009;Widodo et al, 2013), C. striatus (Islam et al, 2013;Sakhare, 2015), and C. Limbata (Khomsab and Wannasri, 2017). Figure 1 clearly shows that the ratio of fecundity to body weight as well as the ratio of fecundity to body length increases proportionally to the time periods of oodev injections given.…”
Section: IIImentioning
confidence: 95%
“…Snakehead (Channa striata Blkr) of family Channidae, is considered as valuable food fish not only in Indonesia (Widodo et al, 2013;Irhamsyah et al, 2017), but also other countries such as Thailand (Khomsab and Wannasri, 2017), Philippines (Jumawan and Seronay, 2017), Vietnam (Quyen et al, 2016), Malaysia (Song et al, 2013), Cambodia (Sinh, 2014), Sri Lanka (Wijeyaratne, 1994), Nigeria (Ama-Abasi and Ogar, 2013), Bangladesh (Islam et al, 2013), India (Kashyap et al, 2014), Pakistan (Najero et al, 2015) and China (Guet al, 2015) due to delicious, high-quality meat fish and availability throughout the year. Snakehead can be commercially cultured in fish farming, earthen ponds, or hapa system (Kumar et al, 2011;Quyen et al, 2016), and culture strategies of them are currently being developed (Xie et al, 2002;Xie et al, 2017;He et al, 2015;Istiyanto and Diana, 2016).…”
Section: Introductionmentioning
confidence: 99%